IoT-based botnet attacks systematic mapping study of literature - Habiba Hamid; Rafidah Md Noor; Syaril Nizam Omar; Ismail Ahmedy; Shaik Shabana Anjum; Syed Adeel Ali Shah; Sheena Kaur; Fazidah Othman; Emran Mohd Tamil (Springer International Publishing, 2024)
Indexed by WOS/SCOPUS/ERA